2018
DOI: 10.1002/jmri.26566
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐forming intrahepatic cholangiocarcinoma: Can diffusion‐weighted imaging predict microvascular invasion?

Abstract: Background Microvascular invasion (MVI) is a risk factor influencing the survival rate of patients with mass‐forming intrahepatic cholangiocarcinoma (IMCC). Purpose To investigate whether diffusion‐weighted imaging (DWI) could be useful in predicting MVI of IMCC. Study Type Retrospective. Subjects Eighty patients with surgically resected single IMCC (21 MVI‐positive lesions and 59 MVI‐negative lesions). Field Strength/Sequence Preoperative hepatic MRI (1.5T), including T1‐ and T2‐weighted images (T1WI, T2WI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 31 publications
2
31
4
Order By: Relevance
“…Our study results show that a higher CA19-9 level (≥37 U/ml) is a risk factor that increase the probability of MVI in patients with ICC. This result is different from that reported by Zhou et al [12]. This difference may be because the date range of the selected cases differs; in addition, as the number of cases in our study is small, some selection bias must be acknowledged.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Our study results show that a higher CA19-9 level (≥37 U/ml) is a risk factor that increase the probability of MVI in patients with ICC. This result is different from that reported by Zhou et al [12]. This difference may be because the date range of the selected cases differs; in addition, as the number of cases in our study is small, some selection bias must be acknowledged.…”
Section: Discussioncontrasting
confidence: 93%
“…1); these patients included 78 male and 30 female patients, with a sex ratio (M:F) of 2.6:1. Among the 108 patients, the imaging findings of 23 patients with ICC have been previously reported [12]. Compared with previous studies, which focused on the measurement of DWI and ADC quantitative values by one MR model, our research focuses on morphological data and a small amount of quantitative data from six different MR models in order to determine whether a correlation exists between MR imaging features and MVI.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some imaging findings, such as "arterial peritumoral enhancement," "tumor margin," and "peritumoral hypointensity on hepatobiliary phase (HBP)," have been reported to be related to MVI in HCC [20]; some studies have shown that "incomplete tumor capsule" has a significant relationship with MVI in HCC [21]. A small number of studies have also used MRI to predict the MVI of massforming intrahepatic cholangiocarcinoma [22]. Currently, almost all the existing MRI studies have only described the imaging features or clinical characteristics of cHCC-CCA compared to those of pure HCC and ICC, usually with a small sample size [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis of MVI often depended on pathological confirmation after liver resection. Recent studies have reported that preoperative diffusion‐weighted imaging can help the diagnosis of MVI in iCCA patients before liver resection, which was conducive to helping surgeons choose the best treatment . Diabetes mellitus was found to be an additional independent risk factor for RFS in iCCA patients and may be related to the reduction in immunity caused by elevated blood sugar.…”
Section: Discussionmentioning
confidence: 99%